2022
DOI: 10.5713/ab.21.0135
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of aerobically treated manure on odorous material emissions from a swine finishing barn equipped with a continuous pit recirculation system

Abstract: This study was conducted to determine reduction of various odorous materials from a swine farm equipped with a continuous pit recirculation system (CPRS) with aerobically treated liquid manure.Methods: CPRS is used in swine farms in South Korea, primarily to improve air quality in pig houses. In this study, CPRS consists of a manure aerobic treatment system and a fit recirculation system; the solid fraction is separated and composted, whereas the aerobically treated liquid fraction (290.0 ± 21.0% per day of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Furthermore, in a previous study, CPRS using aerobically treated liquid swine manure showed a reduction in various odorous materials, such as NH3, H2S, and VOCs [4]. However, in South Korea, because the CPRS system has been operating for a relatively short period, further verification is required.…”
Section: Introductionmentioning
confidence: 92%
See 4 more Smart Citations
“…Furthermore, in a previous study, CPRS using aerobically treated liquid swine manure showed a reduction in various odorous materials, such as NH3, H2S, and VOCs [4]. However, in South Korea, because the CPRS system has been operating for a relatively short period, further verification is required.…”
Section: Introductionmentioning
confidence: 92%
“…We used the same pig finishing confinement building as in the previous study [4] (Table 1, Figure 1).…”
Section: Experimental Farm Continuous Pit Recirculation System and Ex...mentioning
confidence: 99%
See 3 more Smart Citations